Agency Decision-Making Control and Employment Outcomes by Vocational Rehabilitation Consumers who are Blind or Visually Impaired. (November 2013) - Steinman, Bernard A.; Kwan, Ngai; Boeltzig-Brown, Heike; Haines, Kelly; Halliday, John; Foley, Susan M.
Introduction: We hypothesized that consumers who are blind or visually impaired (that is, those who have low vision) who were served by state vocational rehabilitation agencies with decision-making control over administrative functions would experience better vocational rehabilitation outcomes than consumers served by vocational rehabilitation agencies with less control in these areas. Methods: We merged person-level RSA-911 (fiscal year 2010) data with agency-level data collected as part of the National Survey of State Vocational Rehabilitation Agencies, which we conducted in 2011. We employed multilevel modeling, controlling for select person-level characteristics, and agency-level indicators of primary decision-making control by vocational rehabilitation agencies in six key administrative functions: human resources, infrastructure, management information systems, policies and procedures, program evaluation, and purchasing. Dependent variables were measures of "any employment" and "competitive employment" outcomes. Results: We report a positive association between agency decision-making control over policies and procedures and competitive employment outcomes by consumers who were blind (odds ratio = 2.64; 95% confidence interval 1.23–5. 72). Among consumers who are visually impaired, agency decision-making control over human resources was negatively associated with any employment closures (odds ratio = 0.56; 95% confidence interval = 0.36–0.93) and competitive employment outcomes (odds ratio = 0.56; 95% confidence interval = 0.33–0.97). Discussion: Results demonstrate the potential for factors related to agencies, in addition to factors related to individuals, to function as mediators of vocational rehabilitation outcomes for consumers who are blind or visually impaired. Implications for practitioners: Findings highlight the importance of understanding how management control over areas such as policy and procedures have the potential to influence service delivery and subsequent employment outcomes.